"Grafting through" polymerization involving surface‐bound monomers. Issue 2 (5th October 2015) - Datta, Preeta; Genzer, Jan
ABSTRACT: "Grafting through" polymerization represents copolymerization of free monomers in solution and polymerizable units bound to a substrate. Free polymer chains are formed initially in solution and can incorporate the surface‐bound monomers, and thereby, get covalently bonded to the surface during the polymerization process. As more growing chains attach to the surface‐bound monomers, an immobilized polymer layer is formed on the surface. We use a combination of computer simulation and experiments to comprehend this process for monomers bound to a flat impenetrable substrate. We concentrate specifically on addressing the effect of spatial density of the surface‐bound monomers on the formation of the surface‐attached polymers. We employ a lattice‐based Monte Carlo model utilizing the bond fluctuation model scheme to provide molecular‐level insight into the grafting process. For experimental validation, we create gradients of density of bound methacrylate units on flat silicon wafers using organosilane chemistry and carry out "grafting through" free radical polymerization initiated in bulk. We report that the proximity of the surface‐bound polymerizable units promotes the "grafting through" process but prevents more free growing chains to "graft through'' the polymerizable units. The "grafting through" process is self‐limiting in nature and does not affect the overall density of the surface‐bound polymer layer, except in case of the highest theoretical packing density of surface‐bound monomers. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2016, 54, 263–274 Abstract : This snapshot from a typical simulation run shows two chains (red and blue) "grafted through" on the substrate. The substrate‐bound monomers are depicted in a darker hue of the same color. The dark grey spheres represent unused substrate‐bound monomer units.